Comparison of pH Adjustment and Electrocoagulation Processes on Treatability of Metal Plating Wastewater - Kabuk, Harun Akif; Avsar, Yasar; Ilhan, Fatih; Ulucan, Kubra (TAYLOR & FRANCIS INC, 2014)
This study includes both the removal of heavy metals and chemical oxidation demand from metal plating wastewater with pH adjustment and electrocoagulation processes and a comparison of these two processes. For the pH adjustment, process experimental works were studied for five pH levels as 6.0, 7.0, 8.0, 9.0, and 10.0. Optimum removal rates obtained at pH 8.0. With these operating conditions, 90% COD removal, 99.9% Zn (II) removal, 92.5% Cu (II) removal, 78.6% Ni (II) removal, and 50.5% Cr (VI) removal efficiencies were gained. For the electrocoagulation process, the optimum working conditions were found using response surface methodology (RSM) with a 5-level, 6-replicate central composite design (CCD). The optimum working conditions of the electrocoagulation process for pH, reaction time, and current density were determined as 8.0, 90min, and 250A/m ( 2 ), respectively. At this condition, 90% COD, 100% Zn, 97% Cu, 90% Ni, and 75% Cr removal efficiencies were obtained. Treatment costs for each process per unit cubic meter wastewater were calculated as $91 and $34.8.
Keywords: pH adjustment; response surface methodology; heavy metal removal; electrocoagulation; optimization; metal plating wastewater; HEAVY-METALS; REMOVAL; ELECTRODES; EFFLUENT; CR(VI); PRECIPITATION; COAGULATION; CHROMIUM; CU2+; Chemistry; Engineering